Lung function and aerobic capacity in adult patients following modified Fontan procedure. Issue 3 (1st March 2001) - Fredriksen, P M; Therrien, J; Veldtman, G; Warsi, M A; Liu, P; Siu, S; Williams, W; Granton, J; Webb, G
Abstract : OBJECTIVE: To examine cardiopulmonary performance in 52 adult patients with a Fontan circulation. DESIGN: Retrospective cohort study. Values of maximum oxygen uptake (Vo 2 max), maximum heart rate (HRmax), forced vital capacity (FVC), and forced expiratory volume in one second (FEV1 ) were compared with predictive values for different age groups. Patients were further subdivided into those with a pulmonary artery connection (RA–PA) or right atrium to right ventricle conduit (RA–RV). RESULTS: At late follow up (median 10 years, range 1 to 26 years), patients with Fontan circulation had greatly diminished Vo 2 max, HRmax, FVC, and FEV1 compared with predicted values. Early age at surgery had a positive impact on aerobic capacity. The FEV1 :FVC ratio indicated restrictive lung function. No differences were found with respect to any variable between patients with RA–PA connections and those with RA–RV connections. CONCLUSIONS: Patients with a Fontan circulation have greatly diminished values of aerobic capacity and a restrictive pattern of lung function. Patients with an early surgical procedure obtained higher values of Vo 2 max. The theoretical benefits of including the right ventricle in a Fontan circulation were not apparent.